El sinceramiento de la vida privada y la recuperación de lo público. Individuos, prácticas y familia a través de testamentos en Valparaíso de 1860 - Cavieres F, Eduardo (Revista de Historia Social y de las Mentalidades, 2011)
Along with meeting conceptual and methodological pr oblems in relation to the range of the private life history, the article analyses the thin borders between private and public life and the precautions that a historian must take in order to write effectively about what he considers the sphere of a particular and specifics tudy. To illustrate these problems and move from theroretical discussion, the author considers a transitional period in the daily and familiar life of Valparaíso from the middle of the 19 th century, and uses wills of the time as the main sou rce of his study to visualize manners and behaviors that existed within the homes, even though, in many ways, these were just reproductions of the public life.